Case report: Rapid development of amyloid A amyloidosis in temporal arteritis with SAA1.3 allele; An unusual case of intestinal amyloidosis secondary to temporal arteritis - Yoshida, Shuhei; Matsumoto, Haruki; Temmoku, Jumpei; Shakespear, Norshalena; Kiko, Yuichiro; Kikuchi, Kentaro; Sumichika, Yuya; Saito, Kenji; Fujita, Yuya; Matsuoka, Naoki; Asano, Tomoyuki; Sato, Shuzo; et al. (Frontiers in Immunology, 2023)
Temporal arteritis (TA) is a large-vessel vasculitis mostly seen in older patients. Amyloid A (AA) amyloidosis secondary to a chronic inflammation induces multiple organ dysfunctions, including a dysfunction of the gastrointestinal tract. Herein, we present a case of TA complicated by AA amyloidosis that was resistant to oral and intravenous steroids. An 80-year-old man with a history of new-onset headache, jaw claudication, and distended temporal arteries was referred to our department. On admission, the patient presented with tenderness and a subcutaneous temporal nodule in both temple arteries. Ultrasonography of the nodule revealed an anechoic perivascular halo surrounding the right temporal artery. Following the diagnosis of TA, high-dose prednisolone therapy was initiated. However, the patient presented with recurrent abdominal pain and refractory diarrhea. Due to the unclear origin of refractory diarrhea, an extensive workup, including biopsy of the duodenal mucosa, was performed. Endoscopy revealed chronic inflammation in the duodenum. Immunohistochemical analysis of duodenal mucosal biopsy samples revealed AA amyloid deposition resulting in the diagnosis of AA amyloidosis. After tocilizumab (TCZ) administration, refractory diarrhea reduced; however, the patient died of intestinal perforation 1 month after the start of TCZ administration. Gastrointestinal involvement was the main clinical manifestation of AA amyloidosis in the present case. This case highlights the importance of bowel biopsy screening for amyloid deposition in patients with unexplained gastrointestinal tract symptoms, even in a recent onset of large-vessel vasculitis. In the present case, the carriage of the SAA1.3 allele likely contributed to the rare association of AA amyloidosis with TA.